2021
DOI: 10.1097/md.0000000000025497
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liver biochemical abnormality between COVID-19 patients with liver cirrhosis versus COVID-19 alone and liver cirrhosis alone

Abstract: Coronavirus disease (COVID-19) patients frequently develop liver biochemical abnormality. However, liver biochemical abnormality in COVID-19 patients with liver cirrhosis is under-recognized. Patients hospitalized during COVID-19 pandemic in China (ie, from February to April 2020) were screened. All of 17 COVID-19 patients with liver cirrhosis consecutively admitted to the Wuhan Huoshenshan Hospital were identified. Meanwhile, 17 age-, sex-, and severity-matched COVID-19 patients without liver cirrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
(60 reference statements)
3
7
0
Order By: Relevance
“…Similar to our findings, in their study comparing COVID-19-positive and -negative patients, An et al . reported higher CTP scores in COVID-19-positive cirrhosis patients than in COVID-19-negative cirrhosis patients [ 9 ]. The multicentre study by Qi et al ., in turn, evaluated 21 patients who were previously diagnosed with cirrhosis and positive for COVID-19, and identified 16 patients as CTP-A, 3 patients as CTP-B, and 2 patients as CTP-C after identifying COVID-19 positivity [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our findings, in their study comparing COVID-19-positive and -negative patients, An et al . reported higher CTP scores in COVID-19-positive cirrhosis patients than in COVID-19-negative cirrhosis patients [ 9 ]. The multicentre study by Qi et al ., in turn, evaluated 21 patients who were previously diagnosed with cirrhosis and positive for COVID-19, and identified 16 patients as CTP-A, 3 patients as CTP-B, and 2 patients as CTP-C after identifying COVID-19 positivity [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reporting findings in support of our hypothesis, An et al . suggested that COVID-19-positive cirrhosis patients were better able to access healthcare than COVID-19-negative patients, who did not present to hospital unless they there was a worsening in their condition, resulting in more complications [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, the lungs were the most susceptible organ to the COVID-19 infection, followed by the liver. It has been demonstrated in several studies that lung injury by the SARS-COV2 is mediated by attaching its spike protein to the ACE2 receptor [1,6,7]. The ACE2 receptor is, incidentally, highly expressed in alveolar type-II cells, as well as liver and bile duct cells, making it possible for the SARS-COV2 to infect cells in these regions most dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) infection, caused by severe acute respiratory syndromerelated coronavirus 2 (SARS-CoV-2) and leading to severe acute respiratory syndrome, has been spreading rapidly worldwide with a deleterious effect on global health. The disease was first discovered on December 19, 2019, in Wuhan, China [1], which was later declared as a public health emergency by the World Health Organization (WHO) on January 30, 2020. This viral pandemic spreads through respiratory droplets via sneezing and coughing and has an incubation period of approximately 3-5 days [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation